2020
DOI: 10.3389/fbioe.2020.565561
|View full text |Cite
|
Sign up to set email alerts
|

BMSC-Exosomes Carry Mutant HIF-1α for Improving Angiogenesis and Osteogenesis in Critical-Sized Calvarial Defects

Abstract: Repair and reconstruction of critical-sized bone defects has always been a difficult task in orthopedics. Hypoxia inducible factor-1α (HIF-1α) plays an important role in bone defect repair, it has the dual function of promoting osteogenesis and vascular regeneration, but it is quickly degraded by the body under normoxic conditions. Previously we prepared mutant HIF-1α, which has been shown to efficiently maintain cellular expression under normoxic conditions. In this study, we evaluated for the first time the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Recent research has reported that exosomes derived from MSCs have cardioprotective effects by inhibiting cardiomyocyte apoptotic injury [ 25 ]. BMSCs-derived exosomes have been shown to stimulate the proliferation and osteogenic differentiation of BMSCs to promote new bone regeneration and neovascularization in bone defects [ 26 ]. Therefore, exosomes are a cell-free therapeutic that may be safer than direct MSCs therapy and provide a potential modality for tissue regeneration [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has reported that exosomes derived from MSCs have cardioprotective effects by inhibiting cardiomyocyte apoptotic injury [ 25 ]. BMSCs-derived exosomes have been shown to stimulate the proliferation and osteogenic differentiation of BMSCs to promote new bone regeneration and neovascularization in bone defects [ 26 ]. Therefore, exosomes are a cell-free therapeutic that may be safer than direct MSCs therapy and provide a potential modality for tissue regeneration [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural materials include collagen ( Chang et al, 2011 ), gelatin ( Chang et al, 2020 ), fibrin ( Rabbani et al, 2017 ), silk fibroin ( Qing et al, 2018 ), alginate ( Yang et al, 2018 ), gellan gum, hyaluronic acid (HA) ( Yazdani et al, 2019 ), chitosan ( Kim et al, 2016 ), Matrigel ( Wang et al, 2020b ); while synthetic polymer materials include poly caprolactone (PCL) ( Zhang et al, 2017 ), polydimethylsiloxane (PDMS) ( McKee et al, 2017 ), polyethylene oxide (PEO) ( Evrova et al, 2016 ), polylactic acid (PLA) ( Gandolfi et al, 2020 ), poly lactic acid-glycolic acid (PLGA) ( Swanson et al, 2020 ), polyvinyl alcohol (PVA) ( Kalachaveedu et al, 2020 ), polyethylene glycol (PEG), tribasic calcium phosphate (TCP) ( Ying et al, 2020 ). Biomaterials used for 3D bioprinting are called “bio-inks.”…”
Section: Methodsmentioning
confidence: 99%
“… Yang et al (2020b) reported that the combination of UCMSC-derived exosomes and HAP-embedded crosslinked HA-alginate hydrogel in situ significantly enhanced bone regeneration of preosteoblasts. Several studies Qi et al (2016) ; Zhang et al (2016) , and Ying et al (2020) reported that the combination of iPSC- or MSC-derived exosomes and a β-TCP scaffold promoted angiogenesis and osteogenesis. Three studies Sanchez et al (2020) ; Wang et al (2020d) , and Zha et al (2021) reported that the combination of exosomes and a PCL scaffold significantly enhanced osteogenic differentiation of MSCs.…”
Section: Stem Cells (Scs)mentioning
confidence: 99%
“…The incorporation of exosomes derived from bone mesenchymal stem cells (BMSC) and hypoxia inducible factor-1α (HIF-1α) to β-TCP scaffolds significantly repaired rat criticalsized bone defects by facilitating new bone regeneration and neovascularization (Ying et al, 2020). Dental pulp stem cells (DPSCs)-derived extracellular vesicle (EVs)/β-TCP scaffolds was demonstrated to boost bone formation in the periphery of the defects (Imanishi et al, 2021).…”
Section: The Addition Of Stem Cells and Cell-derived Active Substance To Beta-tricalcium Phosphatementioning
confidence: 99%